1985
DOI: 10.1093/oxfordjournals.eurheartj.a061917
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after a controlled randomized post-myocardial infarction rehabilitation programme: effects on morbidity and mortality

Abstract: Prognosis during 4.5 years of follow-up after myocardial infarction (MI) in 2 groups of patients 25 to 65 years of age was related to physical rehabilitation and usual risk factors. We randomized 167 patients to a rehabilitation (R) group and a control (C) group (84 and 83 patients respectively). At the end of the training period, the R group had a significantly higher work capacity, a higher double product reached during the stress test and lower triglycerides. During the 55 months of follow-up after the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…Four years after discharge, 50% of the working-active patients in our study were without a job. Several interventional rehabilitation studies [2][3][4][5][6][7][8][9][10] have failed to show any improvement in the job prognosis. Rehabilitation studies designed to improve the work outcome after MI should be viewed in the light of our study's findings, and should focus mainly on the prognostic factors that we have shown identify high-risk patients with a poorer work outcome after MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four years after discharge, 50% of the working-active patients in our study were without a job. Several interventional rehabilitation studies [2][3][4][5][6][7][8][9][10] have failed to show any improvement in the job prognosis. Rehabilitation studies designed to improve the work outcome after MI should be viewed in the light of our study's findings, and should focus mainly on the prognostic factors that we have shown identify high-risk patients with a poorer work outcome after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional rehabilitation studies, however, have not shown any convincing effect on work outcome [2][3][4][5][6][7][8][9][10]. Rehabilitation programs may not have targeted high-risk groups because of lack of valid data on prognostic factors for retirement.…”
Section: Introductionmentioning
confidence: 99%
“…Five trials elicited no benefit 51 52 53 54 55. All these trials were of different design and used different exercise regimens and durations.…”
Section: Age Limitsmentioning
confidence: 99%
“…The measures used have included work status (e.g. Marra, Paolillo, Spadaccini and Angelino, 1985), physical complaints (e.g. Horlick, Cameron, Firor, Bhalerao and Baltzan, 1984), personality dimensions measured with standardized questionnaires (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mallaghan and Pemberton, 1977;Mayou, 1981), readmission to hospital (e.g. Stern, Pascale and Ackerman, 1977;Marra et al, 1985), physiological effects of the exercise program (e.g. Sivarajan, Bruce, Lindskog, Almes, Belanger and Green, 1982), and mortality (e.g.…”
Section: Introductionmentioning
confidence: 99%